The Assassination Cases of Madan Lal Dhingra, 1909 and Udham Singh, 1940 as Social Drama - Seal, Lizzie (The British journal of criminology, 2024)
There were two Indian nationalist assassinations in London in the twentieth century: Sir William Curzon Wyllie by Madan Lal Dhingra in 1909 and Sir Michael O’Dwyer by Udham Singh in 1940. We read these assassinations as social dramas during which shifting meanings of British imperialism were articulated, contested and reinforced. We compare the cases to examine how Dhingra and Singh’s insistence on the iniquity of colonial violence contested dominant narratives of the British Empire as benign. Capital trials offered Dhingra and Singh the chance to state their views on a public stage. The final act of these social dramas was the death penalty, a measure intended to restore order, but which also posed the risk of turning them into martyrs.